Essays in climate policy and exhaustible resource economics - Jaakkola, NS (2013)
Owners of exhaustible resources will respond to climate policies, and these policies have to take such responses into account. This thesis considers three separate instances in which market power and exhaustible resources interact with climate policy. Chapter 2 considers research and development (R&D;) into green substitutes to oil as a climate policy instrument. Oil exporters will respond to such R&D; efforts in ways which reduce the effectiveness of the policy. Making substitute technologies competitive against current oil prices is not sufficient. R&D; efforts will only force higher oil supplies, aggravating short-term pollution. Eventually, the oil age will end as the substitutes become competitive against the marginal cost of producing oil. This motive encourages an R&D; push to leave more oil underground. Strategic gaming between the importers and exporters may reduce both oil supply and R&D; efforts. Chapter 3 considers fixed costs into opening a deposit of an exhaustible resource. Counterintuitively, a monopolist may invest too early, into too much capacity. I then apply this model to an unconventional exhaustible resource: empty space underground, in which to store captured carbon emissions. I focus on the case of storing European emissions under the North Sea. Monopolistic storage is only a concern if storage space is sufficiently abundant. In this case, the monopolist will not invest enough, to cut back the cumulative storage capacity. Duopolistic storage may involve tacit collusion. Chapter 4 considers an unconventional climate policy instrument: capital income taxes imposed on oil exporters. Such taxes can motivate conservation of polluting resources and allow oil importers to appropriate some oil wealth. These benefits come at the cost of inducing productive distortions, which diminish overall economic output.